SISTEM PENDUKUNG KEPUTUSAN PEMBELIAN SEPEDA MOTOR MENGGUNAKAN METODE ELECTRE - Andrew Andrew; Desi Arisandi; Manatap Dolok Lauro (Fakultas Teknologi Informasi Universitas Tarumanagara, 2020)
This system is built to help candidate of motorcycle buyers to determine which motorcycle is fit for them depending on criteria and their needs. This system uses 9 criteria in purchasing a motorcycle and uses the ELECTRE (Elimination Et Choix Traduisant La Realite) method to produce the best alternative of motorcycle for candidate of motorcycle buyers. The result of making this system are taken based on the average score obtained from the results of the questionnaire distributed to 7 testers. The average score is 40 out of a maximum score of 50 or in percentage is 80%. The accuration of ELECTRE method applied to the system is 100%. From this score, it concludes that application ELECTRE method in this application can quite help candidate of motorcycles buyers to determine best options of motorcycle to be purchased according to their criteria and needs